The MAPK-Signaling Pathway in Colorectal Cancer: Dysregulated Genes and Their Association With MicroRNAs. (24th March 2018) - Slattery, Martha L; Mullany, Lila E; Sakoda, Lori C; Wolff, Roger K; Samowitz, Wade S; Herrick, Jennifer S
Mitogen-activated protein kinase (MAPK) pathways regulate many cellular functions including cell proliferation and apoptosis. We examined associations of differential gene and microRNA (miRNA) expression between carcinoma and paired normal mucosa for 241 genes in the KEGG-identified MAPK-signaling pathway among 217 colorectal cancer (CRC) cases. Gene expression data (RNA-Seq) and miRNA expression data (Agilent Human miRNA Microarray V19.0; Agilent Technologies Inc., Santa Clara, CA, USA) were analyzed. We first identified genes most strongly associated with CRC using a fold change (FC) of >1.50 or <0.67) that were statistically significant after adjustment for multiple comparisons. We then determined miRNAs associated with dysregulated genes and through miRNA:mRNA (messenger RNA) seed region matches discerned genes with a greater likelihood of having a direct biological association. Ninety-nine genes had a meaningful FC for all CRC, microsatellite unstable–specific tumors, or microsatellite stable–specific tumors. Thirteen dysregulated genes were associated with miRNAs, totaling 68 miRNA:mRNA associations. Thirteen of the miRNA:mRNA associations had seed region matches where the differential expression between the miRNA and mRNA was inversely related suggesting a direct association as a result of their binding. Several direct associations, upstream of ERK1/ERK2, JNK, and p38, were found for PDGFRA with 7 miRNAs; RASGRP3 and PRKCB with miR-203a; and TGFBR1 with miR-6071 and miR-2117. Other associations between miRNAs and mRNAs are most likely indirect, resulting from feedback and feed forward loops. Our results suggest that miRNAs may alter MAPK signaling through direct binding with key genes in this pathway. We encourage others to validate results in targeted CRC experiments that can help solidify important therapeutic targets.